CMR, contracts for the international carriage of goods by road - Messent, A. D.; Glass, David A. (Lloyd's shipping law library., 2025)
"Now in its fifth edition, this hallmark text provides a comprehensive, article-by-article guide to the workings of the CMR Convention, as incorporated into English Law by the Carriage of Goods by Road Act 1965. Fully revised throughout, the book offers a complete update of relevant English cases and draws in major developments in the interpretation of the Convention in the case law of other Contracting States. Furthermore, this new edition incorporates two key developments to ensure the book's continuing currency and authority. Firstly, it reviews the operation of the current law following the UK's ratification of the Additional Protocol to the Convention on the Contract for the International Carriage of Goods by Road (CMR) 2008, which provides for the recognition and use of electronic consignment notes, ie e-CMR. Secondly, it addresses the changes consequent on Brexit which affect aspects of the general legal context and whose relationship with the rules of CMR require re-examination, principally in respect of the law governing issues of choice of law, jurisdiction and enforcement of court judgments. Clearly and accessibly written, Messent and Glass continue to offer a level of expert detail and referencing that cannot be found elsewhere. The book is an invaluable reference tool that can be used by the busy legal practitioner, and by other road haulage industry professionals, in any contracting state, to solve the issues that confront them in daily practice. It is also an indispensable guide for academics and students of the international carriage of goods by road"--